2011
DOI: 10.1007/s11224-011-9844-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling trend in diffusion coefficients of low generation G0–G3 PAMAM dendrimers in aqueous solution at high and neutral pH

Abstract: Aqueous solution diffusion coefficients for G0-G3 PAMAM dendrimers were determined from DOSY-NMR spectroscopy at high and neutral pH. The study was performed in a dilute regime and diffusion coefficients at infinite dilution (D 0 ) were estimated from the variation of diffusion coefficients with dendrimer concentration. Hydrodynamic radii (R h ) for each dendrimer were estimated from D 0 using the Stoke-Einstein relationship at both pH. According to D 0 and R h values, the structure of G0-G1 PAMAM dendrimers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…23 Spectra were obtained on a Varian VNMRS 700 apparatus employing DOSY_for_VnmrJ_3.x software. The temperature was set to 30 °C, and samples were allowed to equilibrate for no fewer than 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…23 Spectra were obtained on a Varian VNMRS 700 apparatus employing DOSY_for_VnmrJ_3.x software. The temperature was set to 30 °C, and samples were allowed to equilibrate for no fewer than 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the size of dendrimers is influenced by different pH values . We ignore this in the simple model of dendrimers without atom details, and so did the cited experimental size data of dendrimers which closely match the simulation data.…”
Section: Resultsmentioning
confidence: 96%
“…ϵ is the interaction force parameter. (b) Hydrodynamic radii ( rh) of the dendrimers G1–1, G2–1, G3–1, and G4–1 with fixed branch length from simulations in comparison with dendrimers (PA MAM) in methanol from published experiments in green solid squares fitted by the green solid line, in comparison with PAMAM in aqueous solution from published experiments in green circles fitted by dotted line and green stars fitted by dashed line, and in comparison with those from published simulations 2 in purple and pink. Note here the rh and R g from literatures were scaled for clear comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time correlation function of the scattered intensity, G 2 (t) was analyzed using the inverse Laplace transformation technique (regularized positive exponential sum in our case) to produce the distribution function of decay times. With this, the apparent hydrodynamic radius, R h , can be determined from the decay rate using the Stokes–Einstein equation: Rh=italickTq26italicπηnormalΓ where k is the Boltzmann constant, T is the absolute temperature, η is the solvent viscosity, Γ is the decay rate, and q is the scattering vector (q=4italicπnλsin()θ2, where θ is the scattering angle, n is the refractive index of the solution, and λ is the wavelength of the incident laser light in vacuum).…”
Section: Methodsmentioning
confidence: 99%